Lyotropic liquid crystal composition
A stable lyotropic liquid crystal composition is formed by combining fatty acids or lipids with polyglycerin surfactants and an aqueous component, addressing stability issues and enhancing transdermal absorption in skin preparations and cosmetics.
Patent Information
- Application Number
- JP2024084191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-04
- Filing Date
- 2024-05-23
- Publication Date
- 2025-01-20
AI Technical Summary
Existing lyotropic liquid crystal compositions using polyglycerin surfactants are difficult to stabilize due to polymerization distribution issues and impurities, leading to unstable liquid crystal structures and phase changes, which affect transdermal absorption of active ingredients.
A method involving the combination of fatty acids or lipids bonded with monosaccharides or disaccharides with a polyglycerin type surfactant, optionally with an oily component, and the addition of an aqueous component to form a lyotropic liquid crystal phase, which promotes stable cubic liquid crystal structures for enhanced transdermal absorption.
The composition achieves high compatibility with living organisms and the environment, with lower toxicity and improved transdermal absorption of active ingredients, suitable for use in external skin preparations and cosmetics.
Smart Images

Figure 2025009864000011 
Figure 2025009864000012 
Figure 2025009864000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a lyotropic liquid crystal composition comprising a polyglycerin-type surfactant that is highly compatible with living organisms and the environment. [Background technology]
[0002] It is known that skin topical preparations and cosmetics are composed of compositions containing surfactants, and that by forming the composition into a lyotropic liquid crystal form, the percutaneous absorption of the active ingredient contained in the skin topical preparation or cosmetic or used in combination therewith is promoted. Among lyotropic liquid crystals, compositions in the form of cubic liquid crystals have particularly high percutaneous absorption of the active ingredient. Among many surfactants, polyoxyethylene surfactants, which are widely used, form liquid crystal compositions relatively easily, but there are concerns about their impact on humans and the environment.
[0003] In recent years, environmental problems have become more serious, and polyglycerin-type surfactants have been attracting attention as surfactants made from renewable plant resources rather than petroleum-derived materials, with the aim of achieving the sustainable development goals. Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present disclosure is to provide a lyotropic liquid crystal composition containing a polyglycerin-type surfactant. Although polyglycerin-type surfactants are highly compatible with living bodies and the environment, it has been difficult to stably prepare liquid crystal compositions from such surfactants.
[0005] Polyglycerol fatty acid esters have a structure in which fatty acids are ester-bonded to polyglycerol, which is a polymer of glycerol with hydrophilic groups. Since polyglycerol has multiple hydrophilic groups in its molecule, indiscriminate reactions occur during the synthesis process, resulting in the production of esters containing polyglycerols with a wide range of polymerization distributions and cyclic compounds in which glycerol is dehydrated intramolecularly. Furthermore, due to the similar characteristics of glycerol when esterifying fatty acids with hydrophobic groups, polyglycerol fatty acid esters include not only monoesters but also compounds with different degrees of esterification, such as diesters.
[0006] Lyotropic liquid crystals are formed by the continuous formation of periodic structures within a composition. For example, single compounds such as polyoxyethylene fatty acid esters and polyoxyethylene-polypropylene copolymers, which have a narrow distribution of hydrophilic groups and an easy-to-control degree of esterification, are known to easily form liquid crystal structures and have a stable phase region.
[0007] Even in the case of a lyotropic liquid crystal formed by combining an aqueous component containing a single compound capable of forming liquid crystals, when an oil phase component is blended, the phase region changes, making it difficult to maintain the liquid crystal structure.
[0008] It is known that environmentally friendly commercially available polyglycerol fatty acid esters contain multiple intertwined liquid crystal structures caused by impurities, and it was not previously known that they have a phase region that is stable and has particular transdermal permeability. [Means for solving the problem]
[0009] In view of the above problems, the present inventors have conducted intensive research and found that a composition produced by mixing a fatty acid or lipid bound to a monosaccharide or disaccharide with a polyglycerin surfactant and, if necessary, an oily component, and then adding an aqueous component exhibits a lyotropic liquid crystal form. Furthermore, the present inventors have found that the lyotropic liquid crystal phase promotes the percutaneous absorption of an active ingredient contained in the composition of the present disclosure or used in combination with the composition of the present disclosure, and is less toxic than a conventional composition having a lyotropic liquid crystal phase. Based on this finding, the present inventors have conducted further research and have completed the invention of the present disclosure. That is, the present invention encompasses the following aspects. (Item 1) An oil-based component and a water-based component, or a water-based component and each of the following components: (A) fatty acid or lipid bound to a monosaccharide or disaccharide (B) Polyglycerin-type surfactant A composition comprising one or more of the above and having a lyotropic liquid crystal phase. (Item 2) Next steps 1 and 2: Step 1: Mixing components (A), (B) and, if necessary, an oil component Step 2: Adding an aqueous component to the mixture prepared in step 1 to produce a composition having a lyotropic liquid crystal phase. The composition according to item 1, which is manufactured by (Item 3) The composition according to any of the preceding items, wherein component (A) is a polyglycerol fatty acid ester sugar conjugate. (Item 4) The composition according to any of the preceding items, wherein the polyglycerol fatty acid ester sugar conjugate is polyglyceryl-3 methylglucose distearate. (Item 5) The composition according to any of the preceding items, wherein the polyglycerin type surfactant of component (B) is a polyglycerin fatty acid monoester or a polyglycerin monoalkyl ether. (Item 6) The composition according to any of the preceding items, wherein the degree of polymerization of the polyglycerin is 2 to 20. (Item 7) The composition according to any one of the preceding items, wherein the hydrophobic group of the polyglycerol fatty acid monoester is a fatty acid having 12 to 24 carbon atoms, and the hydrophobic group of the polyglycerol monoalkyl ether is a higher alcohol having 12 to 24 carbon atoms. (Item 8) The composition according to any of the preceding items, wherein the lyotropic liquid crystal phase is a cubic liquid crystal phase. (Item 9) The composition according to any of the preceding items, wherein the composition is a ringing gel. (Item 10) The composition according to any of the above items, characterized in that a lyotropic liquid crystal phase is contained in the composition or promotes percutaneous absorption of an active ingredient used in combination with the composition. (Item 11) 1. A method for producing a composition having a lyotropic liquid crystalline phase, the method comprising: Step 1: Mixing the following components (A), (B) and, if necessary, an oil component: (A) A fatty acid or lipid having one or more monosaccharides or disaccharides bound thereto (B) One or more polyglycerin type surfactants Step 2: Adding an aqueous component to the mixture prepared in step 1 to produce a composition having a lyotropic liquid crystal phase. A method comprising: (Item 1A) Oil-based and water-based ingredients and each of the following: (A) fatty acid or lipid bound to a monosaccharide or disaccharide (B) Polyglycerin-type surfactant The emulsion composition comprises one or more of the above and has a lyotropic liquid crystal phase. (Item 2A) Next steps 1 and 2: Step 1: Mixing components (A), (B) and an oil component Step 2: Adding an aqueous component to the mixture prepared in step 1 to produce an emulsion composition having a lyotropic liquid crystal phase. The emulsion composition according to any of the above items, which is produced by (Item 3A) The emulsion composition according to any of the preceding items, wherein component (A) is a polyglycerol fatty acid ester sugar conjugate. (Item 4A) The emulsion composition according to any one of the preceding items, wherein the polyglycerol fatty acid ester sugar conjugate is polyglyceryl-3 methylglucose distearate. (Item 5A) The emulsion composition according to any one of the preceding items, wherein the polyglycerin type surfactant of component (B) is a polyglycerin fatty acid monoester or a polyglycerin monoalkyl ether. (Item 6A) The emulsion composition according to any one of the preceding items, wherein the degree of polymerization of the polyglycerin is 2 to 20. (Item 7A) The emulsion composition according to any one of the preceding items, wherein the hydrophobic group of the polyglycerol fatty acid monoester is a fatty acid having 12 to 24 carbon atoms, and the hydrophobic group of the polyglycerol monoalkyl ether is a higher alcohol having 12 to 24 carbon atoms. (Item 8A) The emulsion composition according to any one of the preceding items, wherein the lyotropic liquid crystal phase is a cubic liquid crystal phase. (Item 9A) The emulsion composition according to any of the preceding items, wherein the emulsion composition is a ringing gel. (Item 10A) The emulsion composition according to any one of the above items, characterized in that a lyotropic liquid crystal phase is contained in the composition or promotes percutaneous absorption of an active ingredient used in combination with the composition. (Item 11A) A method for producing an emulsion composition having a lyotropic liquid crystal phase, the method comprising the steps of: Step 1: Mixing the following components (A), (B) and an oil component. (A) A fatty acid or lipid having one or more monosaccharides or disaccharides bound thereto (B) One or more polyglycerin type surfactants Step 2: Adding an aqueous component to the mixture prepared in step 1 to produce an emulsion composition having a lyotropic liquid crystal phase. A method comprising: Effect of the Invention
[0010] According to the present disclosure, it is possible to provide a lyotropic liquid crystal composition that is highly compatible with living organisms and the environment, and that is less toxic than conventional compositions having a lyotropic liquid crystal phase and exhibits high percutaneous absorption of active ingredients, and it is possible to produce topical skin preparations and cosmetics containing the composition. [Brief description of the drawings]
[0011] [Figure 1] The figures show the percutaneous absorption of fluorescein in the emulsion compositions produced in Formulation Example 16 and Comparative Example 9. The vertical axis shows the fluorescence intensity, and each measured value is expressed as the average ± standard deviation. The horizontal axis shows the time after the measurement sample was added. The test was performed with n=3, and statistical processing was performed by t-test (*p<0.05, **p<0.001). [Diagram 2] This shows the percutaneous absorption rate of fluorescein in the emulsion composition versus the dilution concentration of the emulsion composition produced in Formulation Example 1 and Comparative Example 10. The vertical axis shows the percutaneous absorption rate (%) (100-(ratio of fluorescence intensity to the control)), and each measured value is expressed as the average ± standard deviation. The test was performed with n=5, and statistical processing was performed using t-test (*p<0.05, **p<0.001, ***p<0.005). [Diagram 3] The figure shows the cell counts relative to the concentration of the emulsion composition added produced in Formulation Example 1 and Comparative Example 10. The vertical axis shows the relative cell counts relative to the number of cells without the addition of the emulsion composition (0%), and the horizontal axis shows the concentration (%) of the emulsion composition in the medium. The test was performed with n=3 for each group, and a significant difference test was performed using Dunnett's multiple comparison with the negative control group (0%), with p<0.05 being considered significant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (definition) It should be understood that the terms used in this specification are used in the sense that they are commonly used in the field unless otherwise specified.Therefore, unless otherwise defined, all technical terms and scientific and technical terms used in this specification have the same meaning as commonly understood by those skilled in the art to which this invention belongs.In case of conflict, this specification (including definitions) shall prevail.
[0013] In this specification, the expressions "contain" and "comprise" include the concepts of "contain", "include", "consist essentially of" and "consist only of".
[0014] In this specification, the expression "and / or" includes both the selection of "and" and the selection of "or." In other words, the expression "A and / or B" includes both the selection of "A or B" and the selection of "A and B."
[0015] In this specification, "liquid crystal" refers to a substance that has both the structural regularity of a crystal and the fluidity of a liquid, and includes thermotropic liquid crystals and lyotropic liquid crystals. Thermotropic liquid crystals refer to a substance that becomes liquid crystal or non-liquid crystal depending on the change in temperature, and lyotropic liquid crystals refer to a substance that becomes liquid crystal or non-liquid crystal depending on the change in solvent concentration.
[0016] In this specification, the term "lyotropic liquid crystal" refers to a liquid crystal formed by adjusting the mixing ratio of an aqueous component, an amphiphilic molecule (such as a surfactant), and an oily component, and has the properties of combining the structural regularity of a crystal with the fluidity of a liquid.
[0017] In this specification, "cubic liquid crystal" refers to a liquid crystal having a structure in which micelles are packed into a cubic lattice, and is classified into a simple cubic lattice, a face-centered cubic lattice, a body-centered cubic lattice, and a hexagonal lattice according to the closest-packed structure.
[0018] In this specification, the term "emulsion composition" refers to a composition containing an aqueous component and an oily component, in which the aqueous component and the oily component are dispersed uniformly.
[0019] In this specification, the term "polyglycerin type surfactant" refers to a surfactant in which polyglycerin and a molecule having a hydrophobic group are bonded via an ester bond or an ether bond.
[0020] In the present specification, the term "oily component" refers to a lipophilic substance, and examples thereof include, but are not limited to, fats and oils, hydrocarbons, silicones, esters, oil-soluble vitamins, etc. Unless otherwise specified, the oily component is a component different from the fatty acid or lipid to which the monosaccharide or disaccharide of the present disclosure is bound.
[0021] As used herein, the term "aqueous component" refers to a hydrophilic substance, including, but not limited to, water, monohydric alcohols, polyhydric alcohols, inorganic salts, water-soluble polymers, and other water-soluble compounds.
[0022] As used herein, the term "ringing gel" refers to a composition that exhibits viscoelastic behavior in the liquid crystalline phase of a liquid solubilized system, and is a firm, highly viscous gel that vibrates in response to physical shock.
[0023] In this specification, the term "fatty acid" refers to a compound having a carboxy group at the end of the hydrocarbon chain. Fatty acids having an unsaturated bond in the hydrocarbon chain are called unsaturated fatty acids, and fatty acids having no unsaturated bonds are called saturated fatty acids.
[0024] In this specification, the term "lipid" refers to a substance that is insoluble in water and soluble in an organic solvent. Examples of lipids include, but are not limited to, esters of alcohol and fatty acid, typically esters of glycerin and fatty acid (triacylglycerol), esters of cholesterol and fatty acid (cholesterol ester) or its hydrolysate (cholesterol), esters of higher alcohol and fatty acid (wax), and phospholipids containing phosphoric acid (e.g., glycerophospholipids, sphingophospholipids).
[0025] As used herein, the term "active ingredient" refers to an ingredient contained in a composition of the present disclosure or used in combination with a composition of the present disclosure in order to exert any intended effect (e.g., improvement, treatment, or prevention of a disease or its symptoms, or a cosmetic effect such as improvement or prevention of wrinkles, blemishes, acne, dry skin, etc.).
[0026] (Liquid crystal composition) The liquid crystal composition of the present disclosure contains a fatty acid or lipid having a monosaccharide or disaccharide bonded thereto, a polyglycerin surfactant, and an aqueous component. The liquid crystal composition of the present disclosure contains an oil component as necessary. The composition of the present disclosure may be emulsified or not emulsified.
[0027] <Liquid crystal> The form of lyotropic liquid crystal varies depending on the components of the composition, and includes cubic liquid crystal, hexagonal liquid crystal, lamellar liquid crystal, reverse hexagonal liquid crystal, reverse cubic liquid crystal, etc. Among cubic liquid crystal, various structures have been found due to close-packed structures (simple cubic lattice, face-centered cubic lattice, body-centered cubic lattice, hexagonal lattice, etc.). Cubic structures are closer to crystalline structures than other lyotropic liquid crystal phases, and are usually very hard due to their high viscoelasticity. Cubic liquid crystals are preferred from the viewpoint of promoting percutaneous absorption of active ingredients contained in the composition of the present disclosure or used in combination with the composition of the present disclosure, and cubic liquid crystals of simple cubic lattice or face-centered cubic lattice are more preferred. The form of liquid crystal can be determined, for example, by polarizing microscope observation, small-angle X-ray scattering measurement, viscosity measurement, and dye staining method.
[0028] Cubic liquid crystals (I1) have a structure in which micelles are packed into a cubic lattice, and inverse cubic liquid crystals (I2) have a structure in which inverse micelles are packed into a cubic lattice. Hexagonal liquid crystals (H1) have a structure in which micelles are packed into a two-dimensional hexagonal lattice, and inverse hexagonal liquid crystals (H2) have a structure in which inverse micelles are packed into a two-dimensional hexagonal lattice. Lamellar liquid crystals (L α ) has a structure in which bilayer membranes are stacked in layers.
[0029] When surfactants are dissolved in water, they exhibit behaviors such as monomolecular dispersion, adsorption (surface adsorption and interfacial adsorption), crystallization, and aggregate formation (micelles and liquid crystals). At low concentrations, surfactants are monodispersed, and as the concentration increases, aggregate formation occurs. The morphology of lyotropic liquid crystals formed in concentrated surfactant systems is described by the hydrophile-hydrophobe balance (HLB) and the critical packing parameter (CPP).
[0030] HLB is an empirical index that represents the ratio of the "size of the hydrophilic group (= head area)" to the "size of the hydrophobic group (= critical chain length)". It ranges from 0 to 20; the closer to 0, the higher the lipophilicity, and the closer to 20, the higher the hydrophilicity.
[0031] If the curvature of the surfactant packing structure that forms the molecular aggregate is defined as "positive curvature" when the hydrophilic groups face outward and "negative curvature" when the hydrophilic groups face inward, the structure formed when the surfactant has a strong hydrophilic group has a positive curvature, and the magnitude of this curvature increases the stronger the hydrophilicity. It can be said that when the hydrophilicity decreases, in other words, when the HLB value decreases, the curvature of the liquid crystal structure changes from positive to negative curvature.
[0032] On the other hand, the packing structure that forms the lyotropic liquid crystal is determined by the volume of the hydrophobic group (ν defined below) and the effective chain length (l defined below). c ), which is expressed by the critical packing parameter (CPP) using the effective cross-sectional area at the interface of the hydrophobic group of the molecular aggregate (a0 defined below). When CPP<1 / 3, the aggregate becomes a cone and forms a spherical micelle, when it is in the range of 1 / 3 to 1 / 2, it forms a truncated cone and a cylindrical micelle, when it is in the range of 1 / 2 to 1, it forms a truncated cone and a flexible bilayer membrane, when it is ~1, it becomes a cylinder and forms a planar bilayer membrane, and when it is >1, it forms an inverted truncated cone and a reverse micelle. When a surfactant forms an aggregate, it takes the most stable form in terms of three dimensions and energy.
[0033] CPP is calculated using the following formula: The length of the hydrophobic part of the surfactant (l c) and its volume (ν), the following formula is given by applying the Tanford equation, where n is the number of carbon atoms in the hydrocarbon chain (alkyl chain, fatty acid chain). l c (Å) = 1.5 + 1.265 n (1) ν(Å) = 27.4 + 26.9 n (2)
[0034] The surface area of a surfactant, or the cross-sectional area per hydrophilic group (a0), is determined by the interactions between the molecules, i.e., van der Waals forces (γa0) and electrostatic repulsions e 2 Since the sum of D / (2εa0) contributes to the chemical potential (μ) of the surfactant in the molecular aggregate, μ is expressed as a function of a0, and if a0 is determined so that the value of μ is minimized, a0 can be obtained as follows: e is the charge per surfactant molecule, γ is the surface tension, D is the thickness of the electric double film at the interface, and ε is the dielectric constant. a0(Å) = √(e2 D / 2εγ) ·····(3)
[0035] The area occupied by one surfactant molecule (a0) and the length of the hydrophobic group (l c The critical packing parameter (CPP), defined as the ratio of the volume of the hydrophobic portion to the volume of a cylinder consisting of the molecular weight (m) and volume (ν), is given by the following equation: CPP = ν / (a0l c ) (4)
[0036] According to the change in CPP, the phase changes from spherical micelles to discontinuous cubic phases to rod-like micellar phases to hexagonal phases to lamellar phases to continuous reversed cubic phases to reversed hexagonal phases to reversed rod-like micellar phases to reversed discontinuous cubic phases to reversed micelles. This also depends on the curvature of the monolayer of the molecular assembly. There have been studies on changing the curvature by adding emulsifiers such as cholesterol and cetanol, and manipulating the morphology of lyotropic liquid crystals. One example of such a study is the combination of hydrogenated lecithin (phosphatidylcholine) and cholesterol, and the addition of cholesterol has been used to change the curvature in the negative direction, and the formation of lamellar liquid crystals and liposomes has been actively studied. Up until now, efforts have been made to make the interfacial membrane flat (forming an infinite periodic structure) by adding highly lipophilic emulsifiers, but there have been fewer studies on changing the curvature in the positive direction compared to the above, and there have been no reports of manipulating the morphology of lyotropic liquid crystals.
[0037] The present inventors have found that by using (A) fatty acids or lipids to which monosaccharides or disaccharides are bound, (B) polyglycerin-type surfactants become cubic liquid crystals rather than hexagonal liquid crystals. Although not wishing to be bound by theory, it is assumed that (A) has a large cross-sectional area of the hydrophilic group (sugar moiety) (large chemical potential), and / or the hydrophilic groups (sugar and polyglycerin) of (A) and (B) having highly hydrophilic side chains repel each other (for example, due to electrostatic interactions and / or steric hindrance), resulting in a larger head (hydrophilic group) area than that of a single substance. As a result, it is believed that when aggregated with (B), the curvature formed by (B) is increased.
[0038] <Fatty acids or lipids bound to monosaccharides or disaccharides> The fatty acid or lipid bound to a monosaccharide or disaccharide is a conjugate in which a monosaccharide or disaccharide is bound to a fatty acid or lipid via an ester bond, ether bond, etc. The conjugate may be a monosaccharide or disaccharide bound to a fatty acid or lipid directly or indirectly, and also includes, for example, a conjugate further bound to polyglycerin, etc.
[0039] Sugars are the initial oxidation products of polyhydric alcohols having multiple hydroxyl groups, and have one formyl group or carbonyl group. They are classified into triose, tetrose, pentose, hexose, heptose, etc. according to the number of carbon atoms. Typical monosaccharides include, but are not limited to, glucose, sucrose, sorbitol, fructose, galactose, mannose, ribose, etc. In the sugars of the present invention, hydrogen or hydroxyl groups may be substituted with methyl groups, etc. In the case of disaccharides, each sugar may be the same or different. Disaccharides are sugars in which two monosaccharide molecules are bound via a glycosidic bond. Glycosidic bonds include, but are not limited to, α(1→1), α(1→2), α(1→3), α(1→4), α(1→5), α(1→6), β(1→1), β(1→2), β(1→3), β(1→4), β(1→5), β(1→6), α(1→1)β, α(1→2)β, etc. A preferred monosaccharide may be glucose, sucrose, or sorbitol. A preferred disaccharide may be mannosylerythritol.
[0040] The fatty acid in the present disclosure may be a saturated fatty acid or an unsaturated fatty acid. In the case of an unsaturated fatty acid, the unsaturated fatty acid may have up to 6 double bonds, preferably 3 or less, more preferably 2 or less. The carbon chain length of the fatty acid may be any length, for example, any length of 8 to 24 carbon atoms. The fatty acid may be a long-chain fatty acid, for example, a fatty acid having 15 to 24 carbon atoms, 15 to 20 carbon atoms, or 15 to 18 carbon atoms. Examples of fatty acids with long carbon chain lengths include, but are not limited to, palmitic acid, stearic acid, arachidic acid, behenic acid, and lignoceric acid. The fatty acid may be a short-chain fatty acid, for example, a fatty acid having 8 to 14 carbon atoms, 9 to 14 carbon atoms, or 10 to 14 carbon atoms. Examples of fatty acids with short carbon chain lengths include, but are not limited to, caprylic acid, capric acid, lauric acid, and myristic acid. The chain length of the preferred fatty acid may be 12 to 16 carbon atoms.
[0041] The lipids in the present disclosure include, but are not limited to, esters of alcohol and fatty acids, glycerides, glycerophospholipids, sphingolipids, sphingophospholipids, cholesterol, etc. The fatty acids constituting the lipids can be any of the fatty acids described above. The preferred lipids can be sphingolipids.
[0042] Examples of fatty acids bound to monosaccharides or disaccharides include stearic acid glucosyl ester, sucrose stearate, sucrose oleate, etc. On the other hand, examples of lipids bound to monosaccharides or disaccharides include glycolipids in which a monosaccharide or disaccharide is bound to a hydrocarbon chain, glyceroglycolipids in which a monosaccharide or disaccharide and a hydrocarbon chain are bound to glycerol, sphingoglycolipids in which a monosaccharide or disaccharide is bound to ceramide, etc.
[0043] As fatty acids or lipids bound to monosaccharides or disaccharides, polyglycerol fatty acid ester sugar conjugates in which monosaccharides or disaccharides, fatty acids, and polyglycerol are bound are preferred. Furthermore, methyl glucose, polyglyceryl-3 in which three molecules of glycerol are polymerized, and polyglyceryl-3 distearate in which two molecules of stearic acid are bound are particularly preferred. The structural formula is shown below (n is the degree of polymerization of glycerol). n is an integer of 2 or more, preferably an integer of 2 to 20, more preferably an integer of 2 to 10, and even more preferably an integer of 4 to 10.
[0044] [ka]
[0045] In a preferred embodiment, the fatty acid or lipid having a monosaccharide or disaccharide attached thereto is selected from the group consisting of polyglyceryl-3 methylglucose distearate, sucrose monostearate, sucrose monostearate, sphingoglycolipids, mannosylerythritol lipids, and combinations thereof.
[0046] <Polyglycerin-type surfactant> A polyglycerin surfactant is a bond in which polyglycerin and a molecule having a hydrophobic group are bonded via an ester bond or an ether bond. Polyglycerin is a polymer of multiple glycerins, and a mixture containing a single or multiple types of polyglycerin with a degree of polymerization of 2 to 20 is preferred. In addition, examples of molecules having a hydrophobic group include molecules having a long-chain alkyl group, typically fatty acids having 12 to 24 carbon atoms and higher alcohols having 12 to 24 carbon atoms, as shown below. The long-chain alkyl group may or may not contain a double bond, and when it contains a double bond, it may have a maximum of 6 double bonds, preferably 3 or less, more preferably 2 or less.
[0047] The polyglycerin surfactant is preferably a polyglycerin fatty acid monoester or a polyglycerin monoalkyl ether. The polyglycerin fatty acid monoester is preferably a fatty acid having a hydrophobic group with 12 to 24 carbon atoms, and examples of fatty acids with 12 to 24 carbon atoms include lauric acid, myristic acid, palmitic acid, stearic acid, isostearic acid, arachidic acid, behenic acid, lignoceric acid, myristoleic acid, palmitoleic acid, sapienic acid, oleic acid, elaidic acid, vaccenic acid, cadreic acid, eicosenoic acid, erucic acid, nervonic acid, linoleic acid, eicosadienoic acid, docosadienoic acid, linolenic acid, pinolenic acid, eleostearic acid, mead acid, dihomo-γ-linolenic acid, eicosatrienoic acid, sucrose ... Examples of the fatty acids include single components of higher fatty acids such as thearidonic acid, arachidonic acid, eicosatetraenoic acid, adrenic acid, bosseopentaenoic acid, eicosapentaenoic acid, osbondoic acid, sardine acid, tetracosapentaenoic acid, docosahexaenoic acid, and herring acid, and mixed components of higher fatty acids derived from vegetable oils and fats such as almond oil, apricot kernel oil, linseed oil, argan oil, apricot kernel oil, olive oil, sesame oil, rice bran oil, pomegranate seed oil, shea butter, coconut oil, watermelon seed oil, macadamia seed oil, castor oil, sunflower seed oil, Brazil nut seed oil, hazelnut seed oil, safflower seed oil, and pumpkin seed oil. The chemical structure of polyglycerin oleic acid monoester is shown below (n is the degree of polymerization of glycerin). n is an integer of 2 or more, preferably an integer of 2 to 20, more preferably an integer of 2 to 10, and even more preferably an integer of 4 to 10. The hydrophobic group may or may not have an unsaturated bond, and may be a straight chain or a branched chain.
[0048] [ka]
[0049] Polyglycerol monoalkyl ether is particularly preferably a higher alcohol having a hydrophobic group of 12 to 24 carbon atoms, and examples of higher alcohols having 12 to 24 carbon atoms include lauryl alcohol, tridecyl alcohol, myristyl alcohol, cetanol, palmitoleyl alcohol, stearyl alcohol, isostearyl alcohol, oleyl alcohol, linoleyl alcohol, elaidolinoleyl alcohol, linolenyl alcohol, elaidolinolenyl alcohol, ricinoleyl alcohol, arachidyl alcohol, behenyl alcohol, erucyl alcohol, and lignoceryl alcohol. Polyglycerol monoalkyl ether is represented by the following general formula (R represents a hydrocarbon group having 12 to 24 carbon atoms, which may be substituted as necessary, and n represents the degree of polymerization of glycerol). n is an integer of 2 or more, preferably an integer of 2 to 20, and more preferably an integer of 2 to 10. Examples include polyglyceryl-4 lauryl ether and polyglyceryl-20 lauryl ether.
[0050] [ka]
[0051] In a preferred embodiment, the polyglycerin type surfactant is selected from the group consisting of polyglycerin-10 monooleate, polyglycerin-10 monolaurate, polyglycerin-5 monooleate, polyglycerin-5 monostearate, polyglycerin-5 monomyristate, polyglycerin-4 lauryl ether, and combinations thereof.
[0052] <Oily ingredients> Examples of oily components include, but are not limited to, vegetable oils such as wheat germ oil, corn oil, sunflower oil, and soybean oil; silicone oils such as dimethicone, methicone, cyclopentasiloxane, cyclohexasiloxane, trimethylsiloxysilicate, diphenyl dimethicone, diphenylsiloxyphenyl trimethicone, and (dimethicone / vinyl dimethicone) crosspolymer; ester oils such as isopropyl myristate, glyceryl trioctanoate, diethylene glycol monopropylene pentaerythritol ether, and pentaerythrityl tetraoctanoate; hydrocarbon oils such as squalane, squalene, liquid paraffin, dodecane, isododecane, polybutene, polyisobutene, and olefin oligomers; and oil-soluble vitamins such as tocopherol, tocotrienol, retinol, tocopherol acetate, and ascorbyl tetrahexyldecanoate. The oil component may be used alone or in combination of two or more kinds.
[0053] <Aqueous component> Examples of the aqueous component include, but are not limited to, water, monohydric alcohols, polyhydric alcohols, inorganic salts, water-soluble polymers, other water-soluble compounds, etc. The polyhydric alcohol is an alcohol having two or more hydroxyl groups, typically an alcohol having 2 to 6 hydroxyl groups.
[0054] Examples of water include, but are not limited to, purified water, ion-exchanged water, ultrafiltered water, reverse osmosis water, distilled water, and other pure water and ultrapure water. One type of water may be used alone, or multiple types may be used in combination.
[0055] Examples of polyhydric alcohols include, but are not limited to, polyalkylene glycols such as diethylene glycol, triethylene glycol, polyethylene glycol, and polypropylene glycol, glycerin, diglycerin, polyglycerin-3, polyglycerin-4, polyglycerin-6, polyglycerin-10, polyglycerin-20, propylene glycol, 1,3-propanediol, 2-butene-1,4-diol, pentane-1,5-diol, 2,2-dimethylpropane-1,3-diol, 3-methylpentane-1,5-diol, pentane-1,2-diol, 2,2,4-trimethylpentane-1,3-diol, 2-methylpropane-1,3-diol, hexylene glycol, 1,3-butylene glycol, and dipropylene glycol. One type of polyhydric alcohol may be used alone, or multiple types may be used in combination.
[0056] Examples of inorganic salts include, but are not limited to, sodium chloride, sodium bromide, potassium chloride, sodium acetate, potassium bromide, calcium chloride, magnesium chloride, zinc chloride, iron chloride, zinc acetate, etc. One type of inorganic salt may be used alone, or multiple types may be used in combination.
[0057] Examples of the water-soluble polymer include, but are not limited to, polyvinyl alcohol, carboxyvinyl polymer, hyaluronic acid, collagen, polylysine, chitosan, polypeptide, oxyethylene-oxypropylene copolymer, acrylic acid / alkyl methacrylate copolymer, alkyl acrylate copolymer, etc. The water-soluble polymer may be used alone or in combination of two or more kinds.
[0058] Other water-soluble compounds include, but are not limited to, urea, organic acids, water-soluble amino acids, vitamins, sugars, and the like.
[0059] The liquid crystal composition of the present invention may contain a fatty acid or lipid having a monosaccharide or disaccharide bonded thereto in an amount sufficient to form a lyotropic liquid crystal, for example, a cubic liquid crystal, a polyglycerin-type surfactant, an oil component, and an aqueous component. Those skilled in the art can appropriately determine the amount of each component sufficient to form a lyotropic liquid crystal, for example, a cubic liquid crystal, using the method of Example 4.
[0060] In one embodiment, in the liquid crystal composition of the present invention, the oil component may be about 10 to about 35% by weight, preferably about 15 to about 30% by weight.
[0061] In one embodiment, in the liquid crystal composition of the present invention, the aqueous component may be about 25 to about 45% by weight, preferably about 30 to about 40% by weight.
[0062] In one embodiment, in the liquid crystal composition of the present invention, the total amount of components A and B can be about 35 to about 55% by weight, and preferably about 40 to about 50% by weight.
[0063] In one embodiment, in the liquid crystal composition of the present invention, component A can be about 2 to about 7% by weight, preferably about 4 to about 5% by weight.
[0064] In one embodiment, in the liquid crystal composition of the present invention, component B can be about 28 to about 53% by weight, preferably about 35 to about 45% by weight.
[0065] (Method for Producing Lyotropic Liquid Crystal Composition) The liquid crystal composition of the present invention is preferably a lyotropic liquid crystal composition produced by a method including the steps of mixing a fatty acid or lipid having a monosaccharide or disaccharide bonded thereto, a polyglycerin-type surfactant, and an oily component, and adding an aqueous component to the mixture to produce a lyotropic liquid crystal composition.
[0066] Components A and B are mixed and stirred at 80°C to obtain a homogeneous solution. Next, the aqueous component heated to 80°C is added and mixed until homogeneous, and then cooled to room temperature while stirring.
[0067] The method of mixing the fatty acid or lipid bound to a monosaccharide or disaccharide, the polyglycerin surfactant, and the oil component is not particularly limited as long as it is a method of stirring with low shear force, and can be appropriately selected depending on the purpose, and examples thereof include manual stirring, a propeller, a disperser, etc. As for the method of forming a liquid crystal by adding an aqueous component to the mixture, the mixture is added to a heated aqueous component while stirring with low shear force to form the desired liquid crystal, thereby producing the liquid crystal composition of the present invention.
[0068] Moreover, the liquid crystal composition of the present invention can be appropriately mixed with fragrances, colorants, preservatives, antioxidants, moisturizing agents, medicines, etc. to produce skin external preparations and cosmetics.
[0069] (Ringing gel composition) A ringing gel is a firm, low-viscosity gel that vibrates and returns to its original configuration when tapped, and is generally formed from a molten cubic phase with a bicontinuous network of branched micelles or a bicontinuous structure. A lyotropic liquid crystal composition forms a ringing gel composition by adjusting the types and amount ratios of the components. EXAMPLES
[0070] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.
[0071] Example 1: Confirmation of liquid crystal structure of emulsion composition An emulsion composition was prepared according to the formulation example shown in Table 1. First, component A, component B, and the oil component were added and stirred and mixed at 80°C to obtain a homogeneous solution. Next, the aqueous component heated to 80°C was added and mixed until homogeneous, and then cooled to room temperature while stirring. The values in Table 1 represent weight percent.
[0072] The liquid crystal structure of the emulsion composition was confirmed by small-angle X-ray scattering using the emulsion composition shown in Table 1 as a measurement sample. A small-angle X-ray scattering apparatus (SAXSpoint 5.0, manufactured by Anton Paar) with a microfocus X-ray source (Cu) was used under measurement conditions of an exposure time of 10 minutes and a camera length of 1,000 mm to obtain a scattering curve, and the scattering vector length (q / nm -1 )(q / nm -1 ) ratio was measured.
[0073] The liquid crystal structure was judged based on the relationship between the scattering vector length of each peak shown in the following formula and the liquid crystal structure (X-ray scattering measurement results), as well as the presence or absence of appearance, spinnability, and echo (ringing). Ringing was confirmed by sealing each emulsion composition in a glass container, clapping the front of the container with one's hand, and checking for the presence or absence of echo. As a result, as shown in Table 2, it was shown that the emulsion compositions of Formulation Examples 1 to 7 were formed of cubic liquid crystals, and were gel-like, spinnable, and ringing gel compositions.
[0074] From these results, cubic liquid crystals are formed by using an oily component of about 10 to about 35% by weight, an aqueous component of about 25 to about 45% by weight, and a total of components A and B of about 35 to about 55% by weight. In one embodiment, component A may be about 2 to about 7% by weight, and component B may be about 28 to about 53% by weight. More preferably, cubic liquid crystals are formed by using an oily component of about 15 to about 30% by weight, an aqueous component of about 30 to about 40% by weight, and a total of components A and B of about 40 to about 50% by weight. In a preferred embodiment, component A may be about 4 to about 5% by weight, and component B may be about 35 to about 45% by weight. Lamella Liquid Crystal: Ratio of scattering vector lengths of each peak = 1:2:3:4 Hexagonal LCD: Ratio of scattering vector lengths of each peak = 1:√3:√2:√7 Cubic LCD: Ratio of scattering vector lengths of each peak = 1:√2:√3:√4 [Table 1] [Table 2] The SAXS measurement results in the table have the following meanings. H: Hexagonal LCD I: Cubic LCD -: Two-phase region where no aggregates can be identified
[0075] Example 2: Study of the combination of components A and B (a) Preparation of emulsion composition An emulsion composition was prepared according to the formulation example shown in Table 3. First, component A, component B, and the oil component were added and stirred and mixed at 80°C to obtain a homogeneous solution. Next, the aqueous component heated to 80°C was added and mixed until homogeneous, and then cooled to room temperature while stirring. The values in Table 3 represent weight percent. [Table 3] *1: The sugars contained are glucuronic acid, glucosamine, galactose, mannose, and glucose. It is a mixture of sphingoglucuronic acid, sphingoglucosamine, and sphingogalactose. The fatty acids contained are fatty acids with 16 to 24 carbon atoms. *2: The fatty acids contained are those with 8 to 14 carbon atoms.
[0076] (b) Evaluation of appearance, shape and physical properties The appearance of each emulsion composition was observed. In addition, the presence or absence of spinnability of each emulsion composition was judged by the touch of the fingers. Furthermore, after sealing each emulsion composition in a glass container, the presence or absence of ringing was judged by clapping the hand on the front of the container.
[0077] As a result, as shown in Table 4, the emulsion composition containing a fatty acid or lipid bound to a monosaccharide or disaccharide (component A) and a polyglycerin type surfactant (component B) was shown to be a gel-like ringing gel composition having spinnability, and to be a cubic liquid crystal. Thus, regardless of the type of component A and component B, cubic liquid crystals can be formed, and any fatty acid or lipid bound to a monosaccharide or disaccharide and any polyglycerin type surfactant can be used, but preferably, component A is selected from the group consisting of polyglyceryl-3 methyl glucose distearate, sucrose monostearate, sucrose monostearate, sphingoglycolipid, mannosyl erythritol lipid, and combinations thereof, and component B is selected from the group consisting of polyglycerin-10 monooleate, polyglycerin-10 monolaurate, polyglycerin-5 monooleate, polyglycerin-5 monostearate, polyglycerin-5 monomyristate, polyglycerin-4 lauryl ether, and combinations thereof. [Table 4]
[0078] (c) Measurement of percutaneous absorption of fluorescein Each emulsion composition was diluted with purified water to prepare a 20% aqueous solution, which was then mixed with an equivalent amount of a 0.2% aqueous solution of fluorescein-Na (manufactured by SIGMA, catalog number: E6377) to prepare a measurement sample. A 0.1% aqueous solution of fluorescein was used as a control measurement sample.
[0079] 20μL of the test sample was dropped onto a film with test paper (Patch Tester "TORII") and applied to the forearm of three subjects for 20 minutes. After lightly rinsing with running water, the forearm was irradiated with an ultraviolet lamp (UVGL-58, UVP) and photographed. The photographed image was binarized, the ratio of the fluorescence intensity to the control was calculated, and the transdermal absorption rate (%) was calculated using the following formula. Percutaneous absorption rate (%) = 100-(ratio of fluorescence intensity to control)
[0080] As a result, as shown in Table 5, it was shown that emulsion compositions (Formulation Examples 1, 8 to 15) containing fatty acids or lipids bound to monosaccharides or disaccharides (Component A) and polyglycerin type surfactants (Component B) promote the percutaneous absorption of fluorescein more than emulsion compositions (Comparative Examples 7 to 8) not containing Component A. The values in Table 5 show the average percutaneous absorption rates. [Table 5]
[0081] Example 3: Formulation Example 16, Comparative Example 9. Comparison of percutaneous absorption of compounds by emulsion compositions manufactured by different processes (a) Preparation of emulsion composition and evaluation of its appearance, shape and physical properties In the formulation shown in Formulation Example 1 in Table 1, emulsion compositions were prepared according to the steps shown in Table 6 (Formulation Example 16 and Comparative Example 9). In both steps, the components were mixed while stirring at 80° C. The appearance of each emulsion composition prepared was observed, and the viscoelasticity and the presence or absence of ringing were evaluated.
[0082] As a result, as shown in Table 6, the emulsion composition produced by the process shown in Formulation Example 16 was shown to be a ringing gel composition that was gel-like and had viscoelasticity. Therefore, it is preferable to add the aqueous component last. [Table 6]
[0083] (b) Measurement of percutaneous absorption of fluorescein Each emulsion composition was diluted with PBS(-) to prepare a 2% solution, which was then mixed with an equivalent amount of a 1% fluorescein-Na PBS(-) solution to prepare a measurement sample, and a 0.5% fluorescein PBS(-) solution was used as a control measurement sample.
[0084] 200μL of the measurement sample was added to the 3D cultured skin LabCyte EPI-MODEL24 6D (J-tec, catalog number: 4111224E) that had been conditioned overnight in a 37℃, 5% CO2 incubator, and the fluorescence intensity (excitation wavelength: 487nm, detection wavelength: 528nm) of the medium (1mL) in the receptor was measured 1, 3 and 6 hours later using a plate reader POWERSCAN HT (DS Pharma Biomedical). The test was performed with N=3.
[0085] As a result, as shown in FIG. 1, it was shown that the emulsion composition prepared by the steps of Formulation Example 16 promoted the percutaneous absorption of fluorescein more than the emulsion composition prepared by the steps of Comparative Example 9.
[0086] Example 4: Examination of the effectiveness of a new emulsion composition and a known composition (a) Preparation of emulsion composition An emulsion composition was prepared according to Formulation Example 1 shown in Table 1 and Comparative Example 10 shown in Table 7. First, component A, component B, and the oil component were added and stirred and mixed at 80°C to obtain a homogeneous solution. Next, the aqueous component heated to 80°C was added and mixed until homogeneous, and then cooled to room temperature while stirring. The values in Table 7 represent weight %. [Table 7]
[0087] (b) Measurement of percutaneous absorption of fluorescein Each emulsion composition was diluted with purified water to prepare 5%, 10%, 15%, and 20% aqueous solutions, which were then mixed with an equivalent amount of a 0.2% aqueous solution of fluorescein-Na (manufactured by SIGMA, catalog number: E6377) to prepare measurement samples. A 0.1% aqueous solution of fluorescein was used as a control measurement sample.
[0088] 20μL of the test sample was dropped onto a film with test paper (Patch Tester "TORII") and applied to the forearm of three subjects for 20 minutes. After lightly rinsing with running water, the forearm was irradiated with an ultraviolet lamp (UVGL-58, UVP) and photographed. The photographed image was binarized, the ratio of the fluorescence intensity to the control was calculated, and the transdermal absorption rate (%) was calculated using the following formula. Percutaneous absorption rate (%) = 100-(ratio of fluorescence intensity to control)
[0089] As a result, as shown in FIG. 2, it was shown that an emulsion composition (Formulation Example 1) containing a fatty acid or lipid having a monosaccharide or disaccharide bonded thereto (Component A) and a polyglycerin-type surfactant (Component B) significantly promoted the percutaneous absorption of fluorescein at a concentration of 5% compared to a known cubic liquid crystal composition (Comparative Example 10) (Patent No. 6019024 specification, which is incorporated herein by reference).
[0090] (c) Comparison of cytotoxicity The cytotoxicity of each composition was compared using immortalized epidermal keratinocytes (PSVK1). PSVK1 cells were plated in a 96-well plate at 5 × 10 4The cells were seeded at a cell density of 10 ... The test was performed with n=3 for each group, and a Dunnett multiple comparison test was used with the negative control group (0%) to determine a significant difference, with p<0.05 being considered a significant difference. As a result, as shown in FIG. 3, Formulation Example 1 showed no toxicity from 0.001% to 0.1%, and a significant difference was observed at 0.5% or more. On the other hand, Comparative Example 10 showed significant toxicity even at 0.001%. In addition, when the half-cytotoxicity concentration (50% inhibition concentrations: IC50) was calculated from the obtained results, Comparative Example 10 was 0.005%, while Formulation Example 1 was 0.445%, showing a difference of 89 times. This shows that Formulation Example 1 has a lower toxicity to epidermal cells than Comparative Example 10, and its safety has been significantly improved. [Industrial Applicability]
[0091] INDUSTRIAL APPLICABILITY The present disclosure can provide a lyotropic liquid crystal composition that is highly compatible with living organisms and the environment and has high transdermal absorption of an active ingredient, and can be used in the cosmetics and pharmaceutical industries.
Claims
1. An oil-based component and an aqueous component, or an aqueous component and each of the following components: (A) fatty acid or lipid having monosaccharide or disaccharide bonded thereto (B) Polyglycerin-type surfactant A composition comprising one or more of the above and having a lyotropic liquid crystal phase.
2. Next steps 1 and 2: Step 1: Mixing components (A), (B) and, if necessary, an oil component Step 2: Adding an aqueous component to the mixture prepared in step 1 to produce a composition having a lyotropic liquid crystal phase. The composition of claim 1 , wherein the composition is produced by
3. 3. The composition according to claim 1, wherein component (A) is a polyglycerol fatty acid ester sugar conjugate.
4. The composition of claim 3, wherein the polyglycerol fatty acid ester sugar conjugate is polyglyceryl-3 methylglucose distearate.
5. 3. The composition according to claim 1 or 2, wherein the polyglycerin type surfactant of component (B) is a polyglycerin fatty acid monoester or a polyglycerin monoalkyl ether.
6. 6. The composition according to claim 5, wherein the degree of polymerization of the polyglycerin is from 2 to 20.
7. 7. The composition according to claim 5, wherein the hydrophobic group of the polyglycerol fatty acid monoester is a fatty acid having 12 to 24 carbon atoms, and the hydrophobic group of the polyglycerol monoalkyl ether is a higher alcohol having 12 to 24 carbon atoms.
8. The composition according to claim 1 or 2, wherein the lyotropic liquid crystal phase is a cubic liquid crystal phase.
9. The composition of claim 1 or 2, wherein the composition is a ringing gel.
10. 3. The composition according to claim 1 or 2, characterized in that a lyotropic liquid crystal phase is contained in the composition or enhances the percutaneous absorption of an active ingredient used in combination with the composition.
11. The composition according to claim 1 or 2, wherein the composition comprises an oil component.
12. The composition comprises: about 35 to about 55 weight percent of the sum of components A and B; About 10 to about 35% by weight of an oil component; about 25 to about 45% by weight of an aqueous component; The composition of claim 11 , comprising:
13. The composition of claim 12, wherein component A is from about 2 to about 7 weight percent and component B is from about 28 to about 53 weight percent.
14. 1. A method for producing a composition having a lyotropic liquid crystalline phase, the method comprising: Step 1: A step of mixing the following components (A), (B) and, if necessary, an oil component. (A) a fatty acid or lipid having one or more monosaccharides or disaccharides bound thereto (B) One or more polyglycerin type surfactants Step 2: Adding an aqueous component to the mixture prepared in step 1 to produce a composition having a lyotropic liquid crystal phase. A method comprising:
Citation Information
Cited By
Hexagonal liquid crystal cleansing gel and preparation method thereof
CN120617064A